Strain-Specific Anti-inflammatory Properties of Two Akkermansia muciniphila Strains on Chronic Colitis in Mice - Zhai, Rui; Xue, Xinhe; Zhang, Liying; Yang, Xin; Zhao, Liping; Zhang, Chenhong (Frontiers in Cellular and Infection Microbiology, 2019)
Akkermansia muciniphila is potential probiotic in that its type strain ATCC BAA-835 has beneficial effects upon obesity and diabetes. However, whether A. muciniphila can improve inflammatory bowel diseases (IBD), which is a form of chronic intestinal dysbiosis, is unknown. Hence, we used an isolated murine A. muciniphila strain (designated 139) and A. muciniphila type strain ATCC, to investigate their anti-inflammatory properties in cell models and in Dextran Sulfate Sodium (DSS)-induced chronic colitis of mice. In vitro, the two A. muciniphila strains exerted similar anti-inflammatory properties as they both reduced IL-8 production by TNF-⍺-stimulated HT-29 cells. However, neither of the strains showed capacity to increase the differentiation of regulatory T (Treg)-cells from CD4+ T cell populations significantly. In vivo, both A. muciniphila strains exerted anti-inflammatory effects on chronic colitis as they improved clinical parameters including spleen weight, colon inflammation index, and colon histological score. They also down-regulated the expression of the pro-inflammatory cytokines including TNF-⍺ and IFN-γ in the colon of mice. However, the anti-inflammatory effects of strain ATCC were stronger than strain 139 in that ATCC significantly reduced spleen weight, colon inflammation index, and fecal lipocalin-2 content in mice with chronic colitis, while strain 139 was not. Dysbiosis of the gut microbiota was observed in mice with chronic colitis. Both A. muciniphila strains facilitated the normalization of the gut microbiota. The specific capacity of strain ATCC to modulate the differentiation of Tregs as well as increase production of short chain fatty acids, demonstrated strain-specific characteristics for these two A. muciniphila strains. This study suggests the potential beneficial effect of A. muciniphila on IBD and the importance of the future study of the function of A. muciniphila at the strain-level.